Mobile Story Making in an Age of Smartphones (Springer International Publishing, 2018)
The participatory turn in media, arts and design along with interrelated developments in the proliferation of social and network media have changed our understanding of the contemporary mediascape. Mobile Story Making in an Age of Smartphones reveals how smartphones and storytelling are forming a symbiosis that empowers twenty-first century citizens and creatives around the world. The edited collection further develops definitions and debate around creative mobile media and its impact on media, art and design. It brings together mobile artists, digital ethnographers, filmmakers working with smartphones, illustrators, screenwriters as well as musicians utilizing apps and mobile devices, who explore new directions in the creative arts with a focus on screen production. Lastly, it demonstrates how mobile devices and smartphones can make a difference in peoples' lives and catalyses creativity in order to tackle current socio-cultural issues.